Determination of site response in Lefkada Town (W. Greece) by ambient variation measurements - Kassaras, I. (31st General Assembly of the European Seismological Commission, 2008)
This study presents results of ambient noise measurements carried out in 78 locations in the town of Lefkada. The horizontal-to-vertical spectral ratios of ambient noise were used to approximate the fundamental resonance frequencies of the subsurface and their associated amplitudes. Summarizing the experiences of different authors with respect to ambient vibration processing, we selected transient free time windows for further analysis. Additionally, we calculated the site responses with respect to the reference site and compared the results with those obtained from the H/V technique. The fundamental frequency and the corresponding amplification factor were calculated for each site. Under the assumption that the H/V spectral ratios of ambient noise coincide with the amplification levels at the dominant frequency of the site response functions, the fundamental frequencies (f0) and amplification factors (A0) were compiled on ARC-INFO GIS software and corresponding maps were developed.